Oxidants and Catalysts in the Aqueous Dissolution of Metal Sulfides: Influence of Electronic Structure on Reactivity - K. Osseo-Asare; F. M. Doyle; E. Peters (Society for Mining, Metallurgy & Exploration, 1993)
With the aid of molecular orbital theory, a discussion is presented of the relationship between the electronic structures of ions and molecules, and the elementary steps involved in homogeneous electron transfer reactions. An electronic theory of the reactivity of oxidants and the mechanism of action of oxidation catalysts is then presented, with emphasis on the oxidative decomposition of metal sulfides. For model oxidants, two molecular reagents: O2 and Cl2, and two ionic reagents: Fe3+ and CU2+ were selected; silver (1) was chosen as the model catalyst. The reactivities of these reagents are rationalized in terms of constraints on orbital overlap, the availability of unoccupied d orbitals, and the rearrangement of electronic configurations.